2020
DOI: 10.1142/s1793545820500108
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative imaging of oral-maxillofacial lesions using optical coherence tomography

Abstract: Histopathological examination is still the gold standard for diagnoses of oral-maxillofacial lesions, but it is invasive and time-consuming. Optical coherence tomography (OCT) provides a kind of noninvasive, label-free, real-time and high-resolution imaging technology. In this study, in order to assess the feasibility of OCT in oral clinical application, fresh excised tissue specimens from 59 patients undergoing oral-maxillofacial surgery were imaged in detail by using a benchtop swept-source OCT system. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…2 and 3, respectively. The discriminator is used to predict the probability that a real HR image IHR is more realistic than an SR image ISR [41]…”
Section: Rrdbmentioning
confidence: 99%
“…2 and 3, respectively. The discriminator is used to predict the probability that a real HR image IHR is more realistic than an SR image ISR [41]…”
Section: Rrdbmentioning
confidence: 99%
“…The layout of the portable SS‐OCT system and its specifications used in the hospital for intraoperative scanning has been reported in our previous articles [21,37,38]. The swept‐source with the output spectral tuning range of 87 nm, centered at 1310 nm, is used, which can provide an output power of 20 mW and a sweep rate of 100 kHz.…”
Section: Methodsmentioning
confidence: 99%
“…In oral medicine, OCT has been used to scan ex vivo and in vivo oral tissues [21‐23]. Hamster cheek pouches with induced dysplasia and malignancies were imaged by using OCT and the feasibility of OCT was evaluated for diagnosis of oral mucosal diseases [24‐26].…”
Section: Introductionmentioning
confidence: 99%
“…24 The previous work of our group showed that OCT images of oral-maxillofacial lesions had obvious distinctions based on different microstructural features. 25 On this basis, we investigated the quantitative difference of OSCC and oral non-cancer tissue based on an available optical attenuation model, and the diagnostic sensitivity (97.88%) and specificity (83.77%) were achieved at the attenuation threshold of 4.7 mm −1 . 26 However, the ability of OCT to distinguish between precancerous lesions and cancer is still unclear, which is more urgent and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Adegun et al quantitatively differentiated dysplasia from normal samples by measuring the rate of change of backscattered light intensity with depth in OCT and histological images 24 . The previous work of our group showed that OCT images of oral‐maxillofacial lesions had obvious distinctions based on different microstructural features 25 . On this basis, we investigated the quantitative difference of OSCC and oral non‐cancer tissue based on an available optical attenuation model, and the diagnostic sensitivity (97.88%) and specificity (83.77%) were achieved at the attenuation threshold of 4.7 mm −1 26 .…”
Section: Introductionmentioning
confidence: 99%